FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN OBESITAS PEGAWAI NEGERI UNIVERSITAS GADJAH MADA YANG MELAKUKAN GENERAL CHECK-UP DI GMC HEALTH CENTER - , SARI NANINGSIH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background:. The prevalence of obesity tend to be higher in the adult population groups who are also more educated, and worked as a civil servant / employee. The higher the level of household expenditure per capita tend to the higher prevalence of obesity. Employee diet consume more foods high in energy, low physical activity and nutritional status of employees, including obesity. Aim : The objective of this study was to determine the factors - factors related to the incidence of obesity UGM public servants who perform medical check-up at the GMC Health Center. Methods: one hundred and seventy-nine employees UGM (n = 179) who did the MCU in the GMC Health Center included in this study. research using obeservasional study design with cross sectional approach. The subject is said to be obese (based Inoue) if BMI â¥ 25. Energy intake data obtained by questionnaire 3 x 24 hour recall. Physical activity data obtained with the IPAQ questionnaire. Data obtained by questionnaire heredity. Further measurements of nutritional status by means of weighing. Results: The results showed that the bivariate there a significant relationship between physical activity with obesity (p = 0.018), there was a significant relationship between hereditary factors to obesity (0.001) and there was no relationship between physical activity with obesity (p = 0.824). The most dominant factor associated with the incidence of obesity is hereditary factors (Î² = 2.261). Conclusion: there is a significant relationship of energy intake with obesity and heredity servants UGM Medical Check up on the GMC health center. However, physical activity was not relationship with obesity